An individual evolutionary learning model meets Cournot - Jasmina Arifovic; Liang Diao; Nobuyuki Hanaki (Osaka University, Institute of Social and Economic Research (ISER), 2023)
In this paper, we extend the individual evolutionary learning model by incorporating other-regarding considerations and apply the model to some Cournot games. Using the model fitted to the experimental data of a repeated 3-player Cournot game (with nonlinear cost and demand functions), we construct out-of-sample predictions regarding the "feedback effects" and "number effects" and test these using data gathered via newly conducted experiments. The prediction regarding the feedback effect is only partially confirmed, being observed for 3- and 4-player games but not the 2-player game. The prediction regarding the number effect is also partially confirmed in that while the model predicts the number effect to be observed with detailed and not aggregate feedback, the effect is observed with both types of feedback.
Keywords: D43; D83; D90; 330; Individual Evolutionary Learning; Oligopoly; Experiment